Increasing palinka recognition with tourism and gastronomy - Harcsa, Imre Milan (Applied Studies in Agribusiness and Commerce, 2017)
The history of Hungarian palinka distillation dates back thousands of years. Palinka is a special product; its quality features are being increasingly recognized and appreciated by consumers. Our national drink went through considerable transformations in the past years, as it left the village environment behind and has become a Hungaricum, popular with young people. The authorization of home distilling in September 2010 was a key factor in its gaining ground in the country. In connection with this topic, the international practice of beverage tourism has been reviewed. After that, the Hungarian practice was examined, including the selection of palinka festivals, thematic palinka tours and palinka product ranges in 19 counties and in Budapest based on a total of 100 restaurants. Using SWOT analysis I revealed the strengths, weaknesses, opportunities and threats of palinka gastronomy and pálinka industry. Overall, it was found that the popularity of pálinka is increasing, but the thematic pálinka tours have not yet widened, and there is a need for more procedures supported by community marketing. JEL Code: Z30, E83